The religious and the religious “nones”: attitudes towards religious practice mediate the relationship between religiousness and subjective mental health - Howie, J. Hunter (Mental health, religion & culture, 2024)
Investigations into the relationship between religiousness and mental health have increasingly focused on nuances between atheists and agnostics (the religious “Nones”). The present study investigates links between religiousness and mental health, and impacts of religiousness on mental health treatment attitudes. Data were analysed for 331 participants recruited online and through social media. Results revealed significantly different ratings of subjective mental health between religious and secular groups. Investigating treatment attitudes revealed significant differences in alternative treatment attitudes between groups; the religious group endorsed alternative treatment attitudes more than agnostics who in turn endorsed these attitudes more than atheists. No significant differences were observed in conventional treatment attitudes. Consequently, a partially latent structural regression model was proposed to investigate the potential mediating role of a latent Traditional Religious Practice factor on the relationship between religiousness and subjective mental health. Results revealed a full mediation effect. Limitations, conclusions, and future directions are discussed.